The contribution of local shrubs to the carbon footprint reduction of traditional dairy systems in Cundinamarca, Colombia - González-Quintero, Ricardo; Sierra-Alarcón, Andrea Milena; Benavides-Cruz, Juan Carlos; Mayorga-Mogollón, Olga Lucía (Springer, 2024)
Cattle farming is responsible for about 15% of Colombia's greenhouse gas emissions (GHGE). In the department of Cundinamarca, specialized dairy farms located in the high tropics contribute 14% of the national milk production, and 94% of them are small-scale producers. Therefore, mitigation strategies for dairy farms are needed to achieve national GHGE reduction targets. This study aims to quantify the carbon footprint (CF), through a Life cycle Assessment Methodology, of 82 specialized dairy farms at the farm gate in 3 regions of Cundinamarca: Central Savannah, West Savannah and Ubate Valley; and to identify the contribution of Acacia decurrens, Baccharis latifolia, and Sambucus peruviana to milk production increases and GHGE mitigation potential. The comparison of the effect of the tree species on the measured variables was carried out by analysis of variance under a completely random design. GHGE were calculated using the 2019 Refinement to 2006 IPCC guidelines and impact factors from databases. The emission factor for enteric methane from cows was estimated by considering the equation proposed by Niu et al. (Glob Chang Biol 24:3368–3389, 2018). The functional units corresponded to one kg fat and protein-corrected milk (FPCM) and one kg live weight gain in a cradle-to-farm-gate approach. For the 3 regions, enteric fermentation and manure left on pasture were the main on-farm sources of GHGE, and feed manufacturing was the main off-farm source. Milk CFs ranged from 1.5 to 2.2 kg CO2-eq kg FPCM−1. The inclusion Acacia decurrens, Baccharis latifolia, and Sambucus peruviana in cattle diets reduced the milk CF by 13–26% and increased milk yield by 19–37% in the three regions. Therefore, the inclusion of locally available forages in dairy cattle diets is a potential sustainable GHGE mitigation option that dairy farmers, from the Colombian high tropics, can adopt.